Murder island [compact disc, unabridged] - Patterson, James, 1947-; Sitts, Brian (Patterson, James, 1947- Doc Savage thriller., 2024)
Professor-turned-crime-fighter Brandt "Doc" Savage and his girlfriend Kira Sunlight believe they've found a utopia on a remote Atlantic island. However, their peace is shattered when they are violently separated and taken to opposite ends of the Earth. Doc's quest to find Kira leads him across Brazil, northern Europe, and the Congo, uncovering a vast global conspiracy far beyond anything he imagined.